Some Matrix Transformations of Convex and Paranormed Sequence Spaces into the Spaces of Invariant Means - M. Mursaleen; S. A. Mohiuddine (Journal of Function Spaces and Applications, 2012)
We determine the necessary and sufficient conditions to characterize the matrices which transform convex sequences and Maddox sequences into 𝑉𝜎(𝜃) and 𝑉∞𝜎(𝜃).